The Effects of the Flash Technique Compared to Those of an Abbreviated Eye Movement Desensitization and Reprocessing Therapy Protocol on the Emotionality and Vividness of Aversive Memories - Brouwers, Thomas C.; de Jongh, Ad; Matthijssen, Suzy J. M. A. (Frontiers in Psychology, 2021)
The Flash technique is a novel intervention aimed at rapidly decreasing the subjective disturbance of an aversive memory, thereby serving as a potential way of treating PTSD. The protocol is used to stimulate clients to engage in positive imagery while being discouraged to actively recollect the targeted disturbing memory. Previous research into the Flash technique’s efficacy shows promising results, yet controlled studies are lacking. To test the efficacy of the Flash technique, it was compared to an abbreviated EMDR therapy protocol in a controlled experimental setting. We hypothesized that the Flash technique would lead to a larger decrease in the emotionality and vividness of an aversive autobiographical memory when compared to EMDR therapy. Our second hypothesis was that the procedure of the Flash technique would be evaluated more pleasant by its receiver. The sample consisted of 60 non-clinical participants (mean age = 25.28 years; 73.33% female) who were able to recall an aversive autobiographical memory. They were randomized to either the Flash technique or the EMDR therapy condition. Measurements consisted of emotionality and vividness-ratings pre and post intervention, and at 1-week follow-up. Bayesian analyses showed no differences between Flash and EMDR to the extent to which the emotionality and vividness of their memory was reduced. Afterwards, the Flash technique was rated more pleasant than EMDR. The results support the claim that the Flash technique might be used as a brief and efficacious intervention for individuals suffering from disturbing memories. Although the results suggest that its efficacy does not differ from EMDR, the Flash technique seems to yield similar outcomes in a more pleasant way. Further research into its working mechanisms and in a clinical sample is required.